PCSK9 deficiency results in increased ectopic fat accumulation in experimental models and in humans - Baragetti, A.; Balzarotti, G.; Grigore, L.; Pellegatta, F.; Guerrini, U.; Pisano, G.; Fracanzani, A.; Fargion, S.; Norata, Giuseppe; Catapano, A. (Sage Publications, 2017)
Â© 2017, Â© The European Society of Cardiology 2017. Background: Proprotein convertase subtilisin kexin type 9 (PCSK9) regulates low-density lipoprotein and very low-density lipoprotein receptor expression in several tissues. Here we evaluated whether PCSK9 may modulate the handling of triglycerides in the liver and peripheral tissues. Methods: Subjects from the PLIC cohort were genotyped for the loss-of-function PCSK9 R46L variant and characterized for clinical and biochemical parameters, total and android fat mass, hepatic steatosis and epicardial fat thickness. Visceral adipose tissue and subcutaneous adipose tissue in PCSK9 KO and wild type mice were quantified by nuclear magnetic resonance imaging. Results: Carriers of the R46L variant (n = 13) had lower low-density lipoprotein cholesterol levels, higher body mass index and increased percentage of total and android fat masses compared with non-carriers (n = 521). R46L variant associated with a two-fold increase prevalence of hepatic steatosis and higher epicardial fat thickness. These observations were replicated in PCSK9 KO mice, which showed increased visceral adipose tissue (but not subcutaneous adipose tissue) when fed chow or high-fat diet for 20 weeks, compared with wild type mice. Conclusions: These data suggest that genetically determined PCSK9 deficiency might be associated with ectopic fat accumulation.